Ultrasound diagnosis of nephrocalcinosis in preterm infants. Issue 1 (January 1988) - Woolfield, N; Haslam, R; Le Quesne, G; Chambers, H M; Hogg, R; Jureidini, K
Abstract : The incidence of nephrocalcinosis in very low birthweight (less than 1500 g) premature infants was assessed by ultrasound scan and analysis of urine. Three of 36 infants had nephrocalcinosis. All had been receiving long term frusemide for bronchopulmonary dysplasia with simultaneous fluid restriction. Urinary investigations showed no consistent findings in babies with nephrocalcinosis.